The dark side of Massive Multiplayers Online Role’s Game (MMORPG) among Malaysian gamer addiction’s and aggressive behaviour: systematic literature review - Zaharim, Ziyad Afiq; Mohd Khir, Azlina; Md Noor, Amna; Borhan, Nik Ahmad Sufian (Human Resource Management Academic Research Society, 2022)
Massively Multiplayer Online Role-Playing Games or MMORPG is a real-time game that requires a strong internet connection and interaction with millions of players. Youths use MMORPG for leisure, stress relief, or to escape their lonely lives by interacting with people in a virtual world. This systematic literature review aimed to study the negative impact of MMORPG addiction among Malaysian youths. Systematic searches of Scopus, SpringerLink, ScienceDirect, Google Scholar, and Dimension database were conducted according to PRISMA guidelines which resulted in more than 13,000 articles, of which seven journal articles met the inclusion criteria. This study identifies negative impacts of MMORPG addiction among Malaysian youths such as psychological distress, depression, poor time management and reducing sense of empathy. We discuss and categorise the findings into two sub-themes: (1) Proactive Action Effects (PAE) and (2) Reactive Action Effects (RAE). We also suggest that each negative impact causes a short- or long-term effect which provides an in-depth understanding of the prediction of aggressive behaviour. This study ends with recommendations for future research.